Honorato Urbano: a performance-ritual do corpo na corda da trasladação do Círio de Nazaré - SILVA, Annaira Etna Rodrigues da (2018)
Webbing and ethnoscenology performance within the context of the transfer of the Candle of Nazareth, in the peculiar rope, where the study of ritual performance-"I promesseiro" and the spectacle of the rope, and also identify the pillars of epistemological ethnoscenology this ritualistic context. Thus, I describe my experiences over 3 consecutive years while promesseira this rope, where part of this research. Along with these descriptions bring the theoretical basis as Performance Studies by Richard Schechner and analysis on Jorge Glusberg Performance of Ethnoscenology of Armindo Biao and the rope Círio Larissa Saré, among other theorists developers of this research. Finally, we affirm the promesseiro as performer and spectacle of bodies Rope of repatriation.